Schenker and Schoenberg: A critical comparison of two analytical methods, with reference to the first movement of Beethoven's Appassionata Sonata. - Hampson, Louise Barbara (My University, 1993)
Schenker and Schoenberg are the two most important and influential theorists of the early twentieth century. Yet Schenker's theory of the Ursatz, or fundamental structure, is viewed by many as contradictory to Schoenberg's Grundgestalt concept. It is remarkable that such brilliant theorists from Vienna could develop such profound and different theoretical concepts. However, In spite of the dispute that is continued to this day among Schenker's and Schoenberg's followers , the two theories need not be considered opposites. This thesis demonstrates , through a critical comparison of two analyses of Beethoven's Appassionata Sonata, that, although the music is approached from different angles, the analyses are not incompatible, but instead are remarkably similar and complementary to one another. Chapter One briefly reviews Schenker's and Schoenberg's theories and outlines important issues concerning the dispute between the two theorists , highlighted in three relatively recent papers. Chapters Two and Three examine two analyses of the Appassionata Sonata, one of which is Schenker's, the other a Schonebergian approach by Patricia Carpenter. It is concluded In Chapter Four that the two theories contain similarities and complementary features which, if used in conjunction with one another, would present a more complete and well-balanced understanding of musical phenomena than either is capable of on its own.
Keywords: Other Music; Other Music